APPEAL‐1: A pan‐European survey of patient/caregiver perceptions of peanut allergy management. Issue 11 (24th June 2020) - Blumchen, Katharina; DunnGalvin, Audrey; Timmermans, Frans; Regent, Lynne; Schnadt, Sabine; Podestà, Marcia; Sánchez, Angel; Couratier, Pascale; Feeney, Mary; Hjorth, Betina; Patel, Ram; Lush, Tessa; et al.
Abstract: Background: Peanut allergy (PA) is associated with marked quality‐of‐life (QoL) impairment. However, data are lacking on the experience and impact of living with PA from the perspectives of persons with PA (PwPA) and their caregivers. A llergy to P eanuts imP acting E motions A nd L ife study 1 (APPEAL‐1) was a pan‐European survey investigating these perspectives. This first of two articles reports clinical characteristics of PwPA and PA management practices. Methods: APPEAL‐1 was a quantitative, online survey conducted in eight European countries, developed by eight representatives of patient advocacy groups and five healthcare professionals and researchers. Eligible participants included adults with PA and parents/caregivers of PwPA who responded by self‐report and provided proxy‐report for the PwPA under their care. Data were summarized using nonweighted descriptive statistics. Results: Of 1846 completed/analysed questionnaires, 528 were from adults with PA (self‐report); 437 by proxy for children with PA (34 aged 0‐3 years, 287 aged 4‐12 years, 116 aged 13‐17 years) and 881 from parents/caregivers (self‐report). Of PwPA (N = 965), 95% reported diagnosis by healthcare professionals, mostly by clinical history and peanut‐specific allergy testing. Rates of allergic rhinitis, asthma and other food allergies in PwPA were 50%, 42% and 79%, respectively. Only 31% of PwPA received HCP advice/support following their worst allergic reaction, and 28% had not been prescribed an adrenaline auto‐injector. Results were similar by country but varied by age group. Conclusions: The APPEAL‐1 findings contribute to greater understanding of PA impact on PwPA, caregivers and family members and the need for improved PA management across Europe. Abstract : The APPEAL‐1 study – pan‐European quantitative investigation of the burdenof living with peanut allergy – provides essential insight on diagnosis and management of peanut allergy. Study results expand our understanding of management of peanut allergy and provide insight into diagnosis, comorbidities, and severity of symptoms. The study suggests a widespread need for improved quality of peanut allergy health management and education. Abbreviations: AAI, adrenaline auto‐injector; HCP, healthcare professional; OFC, oral food challenge; PA, peanut allergy; SPT, skin prick test.